2009
DOI: 10.1007/s10704-009-9337-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature and strain rate on cohesive properties of a structural epoxy adhesive

Abstract: Effects of temperature and strain rate on the cohesive relation for an engineering epoxy adhesive are studied experimentally. Two parameters of the cohesive laws are given special attention: the fracture energy and the peak stress. Temperature experiments are performed in peel mode using the double cantilever beam specimen. The temperature varies from −40 to +80 • C. The temperature experiments show monotonically decreasing peak stress with increasing temperature from about 50 MPa at −40 • C to about 10 MPa at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(42 citation statements)
references
References 26 publications
(45 reference statements)
4
38
0
Order By: Relevance
“…Moreover, temperature and strain rate influence the cohesive laws. In an experimental study (Carlberger et al 2009), it is shown that the peak stress in peel loading decreases monotonically with increasing temperature from −40 • C to +80 • C; the glass transition temperature is about +90 • C for this adhesive. It is also shown that the fracture energy is fairly unaffected by the temperature in this temperature range.…”
Section: Experimental Measurement Of Cohesive Lawsmentioning
confidence: 79%
See 2 more Smart Citations
“…Moreover, temperature and strain rate influence the cohesive laws. In an experimental study (Carlberger et al 2009), it is shown that the peak stress in peel loading decreases monotonically with increasing temperature from −40 • C to +80 • C; the glass transition temperature is about +90 • C for this adhesive. It is also shown that the fracture energy is fairly unaffected by the temperature in this temperature range.…”
Section: Experimental Measurement Of Cohesive Lawsmentioning
confidence: 79%
“…This explains the peel deformation observed in ENFexperiments (Leffler et al 2007), and the shear hackles or cusps observed on fracture surfaces (Pettersson et al 2006). Moreover, if it is assumed that the plasticity is time dependent in nature, it also explains the difference in influence of strain rate on cohesive laws in peel and shear; experiments indicate a much larger rate dependence on the peak stress in shear than in peel (Carlberger et al 2009). With a smaller strain rate and a viscous type of plasticity, more time is available to decrease the stress resulting in a smaller peak stress.…”
Section: Mesomechanical Modellingmentioning
confidence: 89%
See 1 more Smart Citation
“…The authors concluded that the values of r 0 , G Ic , and w decreased with the temperature. The experimental work of Carlberger et al [14] addressed the r 0 and G Ic dependency on temperature of an epoxy adhesive using the DCB test. The tensile cohesive laws of the adhesive were determined by the direct method and the tensile stress, r n vs. w laws showed an approximate triangular shape.…”
Section: Introductionmentioning
confidence: 99%
“…identified a significant reduction on fracture toughness at −196 °C using carbon fiber adherents and an epoxy adhesive (AF-191M) [18]. Carlberger et al has identified that the fracture energy in the epoxy adhesive XW1044-3 is affected significantly at temperatures between −40 and 80 °C [19]. Furthermore, the combined effect of test speed and temperature on the tensile properties of a high-temperature epoxy adhesive have been studied [20] Tensile tests were performed at three different speeds and various temperatures (Room Temperature (RT), 100, 125 and 150 °C), noting that with increasing temperature, the adhesive becomes ductile, resulting in a higher deformation to breakage; the maximum tensile stress decreased linearly with temperature, while increasing logarithmically with the speed test.…”
mentioning
confidence: 99%